The Effect of Poverty on the Provision of Quality Education: A Case of Selected Secondary Schools in Mansa District of Luapula Province, Zambia - Kapasa, Winfridah; Sylvester , Chisebe; Linda, Sibanda (International Journal of Scientific Research and Management (IJSRM), 2023)
The purpose of this study was to examine the effect of poverty on the provision of quality education in selected secondary schools in Mansa. The study was guided by four research objectives and these are; to identify the effect of poverty on the provision of quality education, to examine the effect of poverty in Secondary schools and how it hinders the provision of quality education and to analyze the strategies employed in delivering of quality education in secondary schools. The data collection instrument used in this study was questionnaires and interviews. The study analyzed data using SPSS. Statistical Package for Social Sciences (SPSS) was used as a tool for statistical analysis and the results and was presented in figures and tables. On the effect of poverty in Secondary schools and how it hinders the provision of quality education. Figure 1 shows that schools in poverty-stricken areas may not have enough resources to provide quality education, including textbooks, technology and teaching materials. This can result in inadequate education and reduced learning outcomes for learners. Figure 2 show that poverty can lead to poor health and nutrition, which can negatively affect learners from learning. Figure 3 shows that one of the most important strategies is to have well-trained and qualified teachers who can deliver quality education to learners. These findings suggest that there is a need to dedicate more resources to enable friendly school environment and ensure adequate facilities for inclusive education.